Ketogenic diet prevents paclitaxel‐induced neuropathic nociception through activation of PPARγ signalling pathway and inhibition of neuroinflammation in rat dorsal root ganglion. (2nd August 2021) - Zhong, Shanshan; Zhou, Zhike; Lin, Xinyu; Liu, Fangxi; Liu, Chang; Liu, Zhouyang; Deng, Wenyun; Zhang, Xiuchun; Chang, Hongtao; Zhao, Chuansheng
Abstract: Chemotherapy‐induced peripheral neuropathy (CIPN) is a common side effect during the course of cancer treatment, which is mainly manifested as a series of sensory abnormalities. At present, there are no recommended prevention or treatment strategies, and the underlying mechanisms are unclear. The ketogenic diet (KD), a special diet that is high in fat and low in carbohydrate intake, shows good therapeutic potential in children with epilepsy. In this study, it was found that KD significantly prevented paclitaxel‐induced neuropathic nociception. Using the GSE113941 database, 281 differentially expressed genes (DEGs) were found in an animal model of CIPN and controls. The DEGs were mainly enriched in peroxisome proliferator activated receptor (PPAR) and oxidative phosphorylation signalling pathways. As a main regulatory pathway of lipid metabolism, the PPARγ signalling pathway was significantly upregulated in the KD model. In addition, KD also inhibited the expression of pro‐inflammatory cytokines and the TLR4/NF‐κB signalling pathway in the dorsal root ganglion (DRG) in paclitaxel‐treated rats. In vitro, rat primary DRG neurons were used to investigate the role of PPARγ in paclitaxel‐induced neurotoxicity. It was found that PPARγ agonist rosiglitazone significantly protected DRG neurons against cell apoptosis and reactive oxygen species generation induced by paclitaxel administration. Therefore, KD is a prospective treatment option when applied as a dietary intervention in the prevention and treatment of paclitaxel‐induced neuropathic nociception, possibly through the activation of PPARγ and its neuroprotective functions. Abstract : Ketogenic diet prevents paclitaxel‐induced neuropathic nociception, through activation of PPARγ signalling pathway, as well as inhibition of TLR4/NF‐κB signalling pathway and MCP‐1/IL‐1β secretion, which are upregulated in the dorsal root ganglion of paclitaxel‐induced peripheral neuropathy rats.